Alphaville —insurgent poetry. A portrait of modern nihilism - Gómez Muller, Alfredo (Estudios de Filosofía, 2020)
Jean-Luc Godard’s Alphaville (1965) puts forward a cultural critique of modern capitalism in a poetic form. The film subverts the standard classification of cinematographic “genres” and of cinematographic languages, without separating the content of the criticism from its form of expression. Thus, it uses an original language that integrates both philosophical and poetic referents (Nietzsche, Bergson, Éluard, Borges), putting together elements from the dystopic imagination, the science fiction, the romantic film, and other cinematographic “genres”. Unlike Orwell and Huxley’s dystopias, Alphaville depicts a deeper, insidious, invisible and more efficacious form of totalitarianism that invades the so-called “democratic” societies. This type of totalitarianism is dominated by instrumental rationality and techno-science, which expel art and imagery, the poetic and the possible, emotion, feelings and everything that is free. This paper analyzes the construction of this original form and interprets its critical content from the perspective of Godard’s thought. It is an exercise of looking and knowing how to look.